Impact of Renin-Angiotensin-Aldosterone System Gene Polymorphisms on Left Ventricular Dysfunction in Coronary Artery Disease Patients. Issue 1 (23rd May 2013) - Mishra, Avshesh; Srivastava, Anshika; Mittal, T.; Garg, N.; Mittal, B.
Abstract : Background : Left ventricular dysfunction (LVD), followed by fall in cardiac output is one of the major complications in some coronary artery disease (CAD) patients. The decreased cardiac output over time leads to activation of the renin-angiotensin-aldosterone system which results in vasoconstriction by influencing salt-water homeostasis. Therefore, the purpose of the present study was to explore the association of single nucleotide polymorphisms (SNPs) in angiotensin I converting enzyme; ACE (rs4340), angiotensin II type1 receptor; AT1 (rs5186) and aldosterone synthase; CYP11B2 (rs1799998) with LVD. Methods and results : The present study was carried out in two cohorts. The primary cohort included 308 consecutive patients with angiographically confirmed CAD and 234 healthy controls. Among CAD, 94 with compromised left ventricle ejection fraction (LVEF ≤ 45) were categorized as LVD. The ACE I/D, AT1 A1166C and CYP11B2 T-344C polymorphisms were determined by PCR. Our results showed that ACE I/D was significantly associated with CAD but not with LVD. However, AT1 1166C variant was significantly associated with LVD (LVEF ≤ 45) (p value=0.013; OR=3.69), but CYP11B2 (rs1799998) was not associated with either CAD or LVD. To validate our results, we performed a replication study in additional 200 cases with similar clinical characteristics and results again confirmed consistent findings (p value=0.020; OR=5.20). Conclusion : AT1 A1166C plays important role in conferring susceptibility of LVD.